Republic of Belarus : First Review Under the Stand-By Arrangement, and Request for a Waiver of Performance Criterion, Augmentation of Access, and Modification of Performance Criteria; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the First Review under the Stand-By Arrangement for the Republic of Belarus. All end-March 2009 quantitative and continuous performance criteria and structural benchmarks were met, except for the net international reserves target, which was missed by USD 221 million. A sharp fall in demand for Belarus's exports and a worsening of the capital account has led to the re-emergence of a substantial financing gap for 2009. The authorities have committed to adjust exchange rate and monetary policies, and to maintain a balanced budget despite lower revenue.